Capitalocene Dreams: Dark Tales of Near Futures & The 21st Century Catastrophe: Hyper-capitalism and Severe Climate Change in Science Fiction - Sparks, Catriona Margaret Mullineaux (Curtin University, 2018)
This thesis investigates the research question: What is the role of speculative fiction in a climate changed world? The short story collection: Capitalocene Dreams: Dark Tales of Near Futures explores life on the fringes of disintegrating Australian enclaves during the dying days of neoliberal excess. The exegesis: The 21st Century Catastrophe: Hyper-capitalism and Severe Climate Change in Science Fiction, contrasts ecocatastrophe science fiction of the sixties and seventies with contemporary climate or Anthropocene fiction.